Factors of Deterioration and Their Manifestations on Mural Paintings (Frescoes) in the Hunting Baths of the Ancient City of Leptis Magna, and Methods of Their Prevention: Factors of Deterioration and Their Manifestations on Mural Paintings (Elmergib Journal of Human Sciences, 2026)
The ancient city of Leptis Magna is one of the Roman cities of the Tripolitania region (the Three Cities), renowned for its many prominent archaeological landmarks both inside and outside its walls. These monuments possess significant archaeological and architectural value, distinguished by decorative and artistic elements that reflect the cultural and civilizational creativity of human heritage during the Roman period. This outstanding value prompted UNESCO to inscribe the city on the World Heritage List.This study sheds light on the artistic and technical features of Roman wall paintings (frescoes) in the Hunting Baths at the ancient city of Leptis Magna. It examines the nature of the deterioration factors affecting these paintings, the varying manifestations of their impact, and the resulting negative consequences that have progressively undermined the artistic and architectural integrity of these works. This is particularly evident in the absence of effective scientific and practical conservation measures for the various elements of this cultural heritage, as well as the stagnation in applying preventive procedures and enforcing laws that deter both natural and human-induced deterioration in its different forms. The study also seeks to review available scientific approaches and propose preventive measures to limit the escalation of deterioration factors and to prevent the loss of the artistic features of the mural paintings in the bath complex, as they represent a global cultural and artistic heritage that deserves care and preservation as a cultural legacy for future generations.
Keywords: Roman cities; Tripolitania (the Three Regions); archaeological landmarks; ornamentation